Implementasi Pendidikan Karakter Anak Usia Dini melalui Metode Bermain Peran Usia 5-6 Tahun di Taman Kanak-Kanak An-Nahl Bandar Lampung - Rustamaji, Devi sofa nurhidayah; Cahniyo Wijaya Kuswanto (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2019)
Character education is considered very important to instill in children from an early age. Given the importance of forming these character values, character education can be developed by teachers by implementing character education through role playing methods. The formulation of the problem that the researchers proposed was how to implement character education for early childhood through the role playing method aged 5-6 years in An-Nahl Bandar Lampung Kindergarten. The purpose of this study was to find out about how the implementation of character education through the method of playing the role of early childhood in An-Nahl Bandar Lampung Kindergarten.This research method uses a qualitative descriptive approach involving 1 teacher and the number of 14 children while the object of the research is the implementation of early childhood character education through role playing methods aged 5-6 years at An-Nahl Bandar Lampung Kindergarten, data collected through observation, interviews, and documentation.The results of the study show that the implementation of character education through role playing methods is as follows with the steps: (1) The Teacher Gathered the Children to Give Direction and Rules of the Play, (2) The teacher discusses the Tools that Will Be Used by Children to Play, (3 ) The Teacher Shares the Assignment to Children Before Playing According to Groups To Not Fight, (4) Teachers Gather Children To Be Guided, Give Rules In Games, Accompany And Calculate Children, (5) Educators Only Watch Or Accompany Children In Role Playing, (6 ) Children Play As They Are, Children Can Switch When Bored. Based on the results of the study that the development of the character education of children who have not yet developed (0), began to develop (5), developed according to expectations (6), developed very well (3). This research describes how the teacher processes in implementing child character education and can be used as an alternative source in the process of implementing character education for early childhood.